An account of strategies and innovations for teaching chemistry during the COVID‐19 pandemic - Pilkington, Lisa I. (Biochem Mol Biol Educ, 2021)
The COVID‐19 pandemic led to an abrupt suspension of face‐to‐face teaching activities in higher education institutions across the globe. The instructors and faculty at most institutions have had to adapt, invent, and implement adjustments quickly to adopt an online learning environment. This has been an extraordinarily challenging time for both students and instructors, particularly as many were not aware of the affordances and weaknesses of the online learning environment before it was uptaken. Particularly for chemistry and related disciplines, this change in delivery mode is even more disruptive in courses that have laboratory components due to loss of access to laboratories. As a teaching community, it was our responsibility to respond quickly and effectively to students' learning needs during this unprecedented global crisis. In our course, we provided succinct pre‐recorded lecture‐videos by topic rather than live‐streaming of lectures. The recordings were made available to students a minimum of 24 h before the scheduled lecture time. Students were then provided opportunities to attend live tutorial sessions (held on Zoom and live Q&A feature on Piazza) if they had any questions that they wanted to ask the lecturer directly. We believe that the asynchronous sessions were more equitable than synchronous ones. This meant that students with difficult and challenging home/learning environments (i.e., disruptions at home, work/family schedules, poor internet, limited access to devices, etc.) were minimally disadvantaged. The approach worked well in general for teaching chemistry to pharmacy students and we believe that it can be adopted for other subjects.